Effects of planting window on grain yield and oil yield under rainfed sunflower (Helianthus annuus L.) in Kilwa District, Lindi, Tanzania - Charles O. Joseph; Kassim Kambwily; Sangu M. Emmanuel (Discover Agriculture)
Abstract This study evaluated the effects of planting windows on grain yield and oil yield of three sunflower varieties (Hysun33, Record, and K/Fedha) across two locations in 2023. The two factors (varieties and planting windows) were laid out in a split plot arrangement and fitted into randomized complete block design in three replicates. The first planting window (PW1) occurred in late January, the second (PW2) in mid-February, and the third (PW3) in early March. Weather parameters evaluated included minimum and maximum temperatures, average monthly rainfall and rainfall during the growth period. The weather data revealed trends of decreasing minimum and maximum temperatures, as well as fluctuating average rainfall over the period. Total rainfall did not significantly differ between the three planting windows (PW1, PW2, PW3). However, there was significant variation in rainfall amounts at different phenological stages between planting windows (P = 0.001). Grain yield and oil yield were highest in PW3 (1.50 t/ha and 360.2 L, respectively), as well as for the Hysun33 variety (0.92 t/ha and 22.95 L, respectively). High grain and oil yields were influenced by high germination and survival percentages, high rainfall during leaf development and stem elongation, flowering time and interactions between planting window, variety, and locations. Study showed that PW3 and HYsun33 offers the most favorable options for optimal sunflower production in Kilwa District. However, multi-environment trials, repeated over several seasons is recommended to explore the influence of environmental variables. The results may also prompt a revision of the sunflower planting calendar for the southern zone.